Peningkatan Kemampuan Pengelolaan Homestay Di Desa Wisata Batulayang Kabupaten Bogor Jawa Barat, Indonesia - Dea Prasetyawati; Asep Syaiful Bahri (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2019)
ABSTRACT Batulayang Tourism Village is one of the tourist destinations in the Cisarua area of Bogor Peak. This area actually has good tourism development potential with various tourist objects and attractions including natural potential (landscapes, waterfalls, village, natural atmosphere, rivers), cultural potential (traditional dance, village specialties), artificial tourism (outbound, camping ground, paragliding, hiking, tracking, and tree top). The current condition of Batulayang Tourism Village has been visited by many tourists, however, it still has not been positive for the surrounding community. The surrounding community is more of a spectator and watched by tourists. Even if the community is involved in the management of the tourist area, it will have a positive impact on increasing community income. Community service regarding the improvement of homestay management capabilities in Batulayang Tourism Village, Bogor Regency was attended by 20 homeowners whose homes were willing to be used as homestays. The service method that is carried out is by conducting lectures (counseling), discussions and presentations. The results of this community service are that the provision of knowledge and technology on improving homestay management capabilities in Batulayang Tourism Village, Bogor Regency is well received by the homestay owner and reaches the planned destination. This is indicated by the ability of homestay owners to be able to interact with tourists and provide opportunities for tourists to provide input and advice to homestay owners. In addition, almost the entire implementation of this service has been carried out according to the planning schedule, method, and reseach results; written in 1 paragraph, single space among rows, using past tenseKeywords: Homestay Management, Batulayang Tourism Village, Bogor, West Java, Indonesia  ABSTRAK Desa Wisata Batulayang merupakan salah satau daerah tujuan wisata yang berada di daerah Cisarua Puncak Bogor. Kawasan ini sesungguhnya memiliki potensi pengembangan wisata yang baik dengan adanya berbagai obyek dan atraksi wisata diantaranya adalah potensi alam (bentang alam, air terjun, suasana alam desa, sungai), potensi budaya (tari tradisonal, kuliner khas desa), wisata buatan (outbond, camping ground, paralayang, hiking, tracking, dan tree top). Kondisi saat ini Desa Wisata Batulayang telah banyak dikunjungi oleh wisatawan, namun demikian masih belum bermpak positif bagi masyarakat sekitar. Masyarakat sekitar lebih banyak menjadi penonton dan di tonton oleh para wisatawan. Padahal jika masyarakat tersebut dilibatkan dalam pengelolaan kawasan wisata maka akan memberikan dampak prositif bagi peningkatan pendapatan masyarakat. Pengabdian kepada masyarakat mengenai peningkatan kemampuan pengelolaan homestay di Desa Wisata Batulayang Kabupaten Bogor diikuti oleh 20 pemilik rumah yang rumahnya bersedia dijadikan sebagai homestay. Metode pengabdian yang dilakukan yakni dengan melakukan ceramah (penyuluhan), diskusi dan presentasi. Adapun hasil dari pengabdian kepada masyarakat ini adalah bahwa  pemberian ilmu pengetahuan dan teknologi mengenai peningkatan kemampuan pengelolaan homestay di Desa Wisata Batulayang Kabupaten Bogor diterima dengan baik oleh pihak pemilik homestay dan mencapai tujuan yang sudah direncanakan sebelumnya. Hal ini ditandai dengan kemampuan para pemilik homestay untuk dapat berinteraksi dengan wisatawan serta memberikan kesempatan untuk para wisatawan dalam memberikan masukan serta saran kepada pemilik homestay. Selain itu,  Hampir keseluruhan pelaksanaan pengabdian ini sudah terlaksana sesuai jadwal perencanaanKata kunci: Pengelolaan Homestay, Desa Wisata Batulayang, Bogor, Jawa Barat, Indonesia.